Glomerular endothelial glycocalyx-derived heparan sulfate inhibits glomerular leukocyte influx and attenuates experimental glomerulonephritis - Maciej-Hulme, Marissa L.; Van Gemst, Jasper J.; Sanderson, Patience; Rops, Angelique L. W. M. M.; Berden, Jo H.; Smeets, Bart; Amster, I. Jonathan; Rabelink, Ton J.; Van Der Vlag, Johan (Frontiers in Molecular Biosciences, 2023)
Proliferative forms of glomerulonephritis are characterized by the influx of leukocytes, albuminuria, and loss of kidney function. The glomerular endothelial glycocalyx is a thick carbohydrate layer that covers the endothelium and is comprised of heparan sulfate (HS), which plays a pivotal role in glomerular inflammation by facilitating endothelial-leukocyte trafficking. We hypothesize that the exogenous glomerular glycocalyx may reduce the glomerular influx of inflammatory cells during glomerulonephritis. Indeed, administration of mouse glomerular endothelial cell (mGEnC)-derived glycocalyx constituents, or the low-molecular-weight heparin enoxaparin, reduced proteinuria in mice with experimental glomerulonephritis. Glomerular influx of granulocytes and macrophages, as well as glomerular fibrin deposition, was reduced by the administration of mGEnC-derived glycocalyx constituents, thereby explaining the improved clinical outcome. HSglx also inhibited granulocyte adhesion to human glomerular endothelial cells in vitro. Notably, a specific HSglx fraction inhibited both CD11b and L-selectin binding to activated mGEnCs. Mass spectrometry analysis of this specific fraction revealed six HS oligosaccharides, ranging from tetra- to hexasaccharides with 2–7 sulfates. In summary, we demonstrate that exogenous HSglx reduces albuminuria during glomerulonephritis, which is possibly mediated via multiple mechanisms. Our results justify the further development of structurally defined HS-based therapeutics for patients with (acute) inflammatory glomerular diseases, which may be applicable to non-renal inflammatory diseases as well.